The Image of the Opera in the History of Painting: Delacroix and Rossini S Otello (Global Journal of Human-Social Science, 2014)
The analyzed pictures are "Desdemona cursed by her father" and "Otello and Desdemona.
Keywords: delacroix; rossini; shakespeare; othello; desdemona; opera; theater; iconography